Analysis of Sports Injuries in Review of Types of Injuries and Body Parts Where Injury Occurs in Athletes of Tarung Degrees, Bantul Regency in Preparation for Porda 2022 - Muhammad Romadhoni; Ardhika Falaahudin; Dody Tri Iwandana (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
This study was conducted to determine the injuries that are often experienced by fighting athletes in Bantul Regency and also to determine the location of the injuries experienced by athletes in preparation for the 2022 Regional Police. The subjects in this study were combat athletes in Bantul Regency, which collected 12 people. in collecting data in this study using a questionnaire questionnaire, the results of the study showed several technical injuries that often occur in nature such as during matches, injuries to the head and face such as bruises, abrasions, and fractures then injuries to parts such as bruises, abrasions and fractures. then in the arms such as bruises, abrasions, fractures, dislocations, sprains and strains then also injuries in the heels and feet such as bruises, abrasions, fracture dislocations, sprains, strains and spasms. and for the location of injuries that often occur in the arms and hands